Prevalence, Patterns and Correlates of Cigarette Smoking in Male Adolescents in Northern Jordan, and the Influence of Waterpipe Use and Asthma Diagnosis: A Descriptive Cross-Sectional Study - Al-Sheyab, Nihaya (MDPI, 2014)
Our study investigates the prevalence, patterns and predictors of tobacco smoking among early adolescent males in Northern Jordan and whether asthma diagnosis affects smoking patterns. A descriptive cross sectional design was used. Males in grades 7 and 8 from four randomly selected high schools in the city of Irbid were enrolled. Data on waterpipe (WP) use and cigarette smoking patterns were obtained (n = 815) using a survey in Arabic language. The overall prevalence of ever having smoked a cigarette was 35.6%, with 86.2% of this group smoking currently. Almost half of the sample reported WP use. The most common age in which adolescents started to experiment with cigarettes was 11–12 years old (49.1%), although 10 years was also common (25.3%). Significant predictors of male cigarette smoking were WP use (OR = 4.15, 95% CI = 2.99–5.76), asthma diagnosis (OR = 2.35, 95% CI = 1.46–3.78), grade 8 (OR = 1.52, 95% CI = 1.10–2.11), and having a sibling who smokes (OR = 2.23, 95% CI = 1.53–3.24). However, this cross-sectional study cannot establish causality, thus longitudinal studies are needed. Public health programs and school-based anti-tobacco smoking interventions that target children in early years at high schools are warranted to prevent the uptake of tobacco use among this vulnerable age group. High school students with asthma should be specifically targeted.